2020
DOI: 10.29244/jp2wd.2020.4.2.74-83
|View full text |Cite
|
Sign up to set email alerts
|

Dana Desa dan Status Desa di Provinsi Jawa Tengah

Abstract: Village Funds and Village Status in Central Java Province Year 2019 is the fifth year of implementation of village fund in Indonesia. At the beginning of its implementation in 2015, village funds were budgeted at IDR 20.8 trillion, which has increased to 3.5 times and reaching about IDR 70 trillion in 2019. This research is aimed to describe village funds and villages status in Central Java Province and the relationship between them. Data to be used are secondary data consisting of village funds and vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
7
1
2
Order By: Relevance
“…Previous research in Central Java Province showed that in 2019 there was a 3.5-fold increase in village funds and the results of the study with regression analysis showed that changes in the amount of the Village Fund budget had no significant effect on changes in village status in Central Java Province (Yulitasari & Tyas, 2020). Previous research in Cibuaya Village, Karawang Regency, revealed that there were obstacles to understanding and implementing regulations, and an error occurred in examining the allocation of funding sources in the implementation of Direct Cash Assistance (BLT) during the Covid-19 Pandemic (Noviyanti et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…Previous research in Central Java Province showed that in 2019 there was a 3.5-fold increase in village funds and the results of the study with regression analysis showed that changes in the amount of the Village Fund budget had no significant effect on changes in village status in Central Java Province (Yulitasari & Tyas, 2020). Previous research in Cibuaya Village, Karawang Regency, revealed that there were obstacles to understanding and implementing regulations, and an error occurred in examining the allocation of funding sources in the implementation of Direct Cash Assistance (BLT) during the Covid-19 Pandemic (Noviyanti et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…Of the two indices, the government often uses the IDM because IDM includes 22 variables and 52 indicators designed in a synergy between economic, social, and ecological aspects that will capture the potential and ability of the village to meet village needs so that welfare can be achieved. Thus, IDM describes the village's status more because of its completeness and up-to-date (Supriadi, 2021;Yulitasari & Tyas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The education level is one factor that affects the ability of the village apparatus (Rodiyah et al, 2021). The educational support of the village head also has a significant (Gani et al, 2020;Arina et al, 2021;Ramly et al, 2019;Tambunan et al, 2020;Yulitasari & Tyas, 2020), but the research has a level of significance different. One of the results that were not significant was the research by Yulitasari & Tyas (2020) in all districts/cities in Central Java Province in 2018-2019, which found that changes in the amount of Village Funds did not significantly affect changes in village status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations